Mídias tecnológicas e educação física escolar - Tofanelli, Higor Augusto [UNESP] (Universidade Estadual Paulista (Unesp), 2018)
This research addresses the use of technological media in Physical School Education. It aims to identify and analyze the use of technological media in the teaching and learning process by teachers in the Physical Education classes in Elementary and Middle School in the city of Tanabi-SP. With specific objectives, to identify teachers' opinions regarding the inclusion of technological media in the didactic-pedagogical process of Physical Education, to verify which technological media are used by Physical Education teachers and how they are incorporating such technologies into the classes and to analyze the implications of the technological media in relation to the motivation and participation of the students in the classes of Physical Education. The research was qualitative in nature and seven teachers from the Tanabi-SP public school, both municipal and state, participated in the study through a semi-structured interview, two females and five males, aged between 28 and 68 years. It was verified by the study that the teachers use the technological media in the classroom, but they do not use them every day. They argued as their main reasons for their use, the concern with the formation of the critical student, so that the student knows how to use the media beyond the school. The main reasons for the lack of use were the lack of teacher training and difficulties in achieving the release of internet access for use in school, making it even more difficult to release when it comes to Physical Education. The study shows that courses for teacher training with the media theme already exist, but are rarely divulged or sought by teachers, the municipality and the state, which attributes to the media the characteristic of use in an informal way... (Complete abstract electronic acess below)

Esta pesquisa aborda a utilização das mídias tecnológicas na Educação Física Escolar. Objetiva identificar e analisar a utilização das mídias tecnológicas no processo de ensino e aprendizagem pelos professores nas aulas de Educação Física no Ensino Fundamental e Médio do município de Tanabi-SP. Tendo como objetivos específicos, identificar a opinião dos professores quanto à inclusão das mídias tecnológicas no processo didático-pedagógico da Educação Física, verificar quais mídias tecnológicas são utilizadas pelos professores de Educação Física e de que forma estão incorporando tais tecnologias às aulas e analisar as implicações das mídias tecnológicas em relação à motivação e participação dos alunos nas aulas de Educação Física. A pesquisa é de natureza qualitativa e participaram do estudo sete professores da rede pública de Tanabi-SP, municipal e estadual, por meio de uma entrevista semiestruturada, sendo dois do sexo feminino e cinco do sexo masculino, com idades entre 28 e 68 anos. Foi constatado pelo estudo que os professores utilizam as mídias tecnológicas em sala de aula, porém não as utilizam de forma cotidiana. Alegaram como principais motivos de utilização, a preocupação com a formação do aluno crítico, para que o aluno saiba utilizar as mídias além da escola. Os principais motivos da não utilização foram a falta de capacitação do docente e dificuldades em conseguir a liberação de acesso à internet para a utilização na escola, dificultando ainda mais tal liberação quando se trata da Educação Física Escolar. Constata-se com o estudo que cursos para capacitação docente com a temática das mídias já existem, porém são pouco divulgados ou procurados pelos professores, pelo município e pelo estado, o que atribui às mídias a característica de utilização de modo informal... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Comunicação; Ensino; Aprendizagem; Educação física (Ensino fundamental); Educação física (Ensino médio); Communication